2006
DOI: 10.1136/oem.2006.026823
|View full text |Cite
|
Sign up to set email alerts
|

The impact of late career job loss on myocardial infarction and stroke: a 10 year follow up using the health and retirement survey

Abstract: Results suggest that the true costs of late career unemployment exceed financial deprivation, and include substantial health consequences. Physicians who treat individuals who lose jobs as they near retirement should consider the loss of employment a potential risk factor for adverse vascular health changes. Policy makers and programme planners should also be aware of the risks of job loss, so that programmatic interventions can be designed and implemented to ease the multiple burdens of joblessness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
2
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 43 publications
8
96
2
5
Order By: Relevance
“…Bamia et al (2008) find that the risk of all-cause mortality is significantly higher for retirees than for older workers still engaged in economic activity. This finding is consistent with the results of Gallo et al (2006), who argue that job loss increases individuals' risk of cardiovascular disease and therefore has detrimental effects on the health of older workers. Morris et al (1994) also find increases risk of cardiovascular disease for the UK.…”
Section: Introductionsupporting
confidence: 92%
“…Bamia et al (2008) find that the risk of all-cause mortality is significantly higher for retirees than for older workers still engaged in economic activity. This finding is consistent with the results of Gallo et al (2006), who argue that job loss increases individuals' risk of cardiovascular disease and therefore has detrimental effects on the health of older workers. Morris et al (1994) also find increases risk of cardiovascular disease for the UK.…”
Section: Introductionsupporting
confidence: 92%
“…This is in contrast to the United States Health and Retirement Survey which concluded that involuntary job losses can double the risk of AMI [17]. It is evident that losing a job increases the risk of developing AMI [18] The results of INTERHEART study [4] although were positive for an association between loss of job and AMI but it showed lower risk compared to other psychosocial risk factor for AMI.…”
Section: Discussioncontrasting
confidence: 46%
“…A meta-analysis including data gathered all over the world (particularly in the USA and Europe) on cancer 51.9% (28) 16.7% (9) 31.5% (17) 24.1% (13) 27.8% (15) 22.2% (12) 14.8% (8) 11.1% (6) Women (n = 50) *1 66.0% (33) 14.0% (7) 20.0% (10) 24.0% (11) 30.0% (15) 30.0% (15) 6.0% (3) 10.0% (5) and (30). In contrast, a Swedish study that investigated the impact of job loss as a result of company closures found no increase in hospital admissions due to heart attacks or strokes (21).…”
Section: Cancermentioning
confidence: 99%